2015
DOI: 10.1021/nl504636x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Photonic Quantum Polarization Entanglement in a Nanoscale Hybrid Plasmonic Waveguide

Abstract: Photonic quantum technologies have been extensively studied in quantum information science, owing to the high-speed transmission and outstanding low-noise properties of photons.However, applications based on photonic entanglement are restricted due to the diffraction limit. In this work, we demonstrate for the first time the maintaining of quantum polarization entanglement in a nanoscale hybrid plasmonic waveguide composed of a fiber taper and a silver nanowire. The transmitted state throughout the waveguide h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…These configurations require top-down nanofabrication. As an alternative, silver nanowires (Ag NWs) synthesized using wet chemistry approaches have proved useful for optical confinement applications below the diffraction limit and for the guiding of light on the nanometre scale, due to their properties of single crystallinity and atomic surface smoothness [12][13][14][15][16][17][18]. There are numerous results on SPP waveguides made of Ag NWs.…”
Section: Introductionmentioning
confidence: 99%
“…These configurations require top-down nanofabrication. As an alternative, silver nanowires (Ag NWs) synthesized using wet chemistry approaches have proved useful for optical confinement applications below the diffraction limit and for the guiding of light on the nanometre scale, due to their properties of single crystallinity and atomic surface smoothness [12][13][14][15][16][17][18]. There are numerous results on SPP waveguides made of Ag NWs.…”
Section: Introductionmentioning
confidence: 99%
“…[63][64][65] Since then, several breakthroughs such as single excitonplasmon-photon conversion, [ 66 ] single-photon sources, [67][68][69][70] and single-photon transistors [ 71 ] have been reported. Recently, M. Li et al [ 72 ] demonstrated the maintaining of quantum polarization entanglement in both dielectric and plasmonic waveguides. They used two polarization-entangled photons to perform quantum state tomography [ 73 ] and the Clauser-Horne-Shimony-Holt (CHSH) inequality test, [ 74 ] which can reveal the quantum properties of the output photons.…”
Section: Movable Effi Cient Couplersmentioning
confidence: 99%
“…[ 76 ] Taking the guiding loss from AgNW into consideration, the coupling effi ciency between fi ber and AgNW is estimated to be as high as 92%. Based on this [ 72 ] Copyright 2015, American Chemical Society. c) Si 3 N 4 waveguide delivers photon pairs to a DC made of dielectric-loaded hybrid waveguides.…”
Section: Movable Effi Cient Couplersmentioning
confidence: 99%
“…[17] To compensate for this, different kinds of approaches to enhancing the emission of monolayer MoS 2 are proposed, including chemical doping, [18] polymeric nano-spacing, [19] defect engineering, [20] and using surface plasmon polaritons (SPPs). [21][22][23] Among these methods, SPPs which have been widely utilized for strong light-matter interaction applications such as photoluminescence enhancement [24][25][26][27][28][29][30][31] and surface enhanced Raman scattering, [32,33] could induce hot electrons and cause the phase transition of MoS 2 , [34][35][36] resulting in the enhanced PL in a metal-MoS 2 coupled system. [37][38][39][40] For example, gap plasmons have been used in different areas, such as enhancing local chemical reactions, [41] dielectric gratings, [42,43] plasmonic nanocavities, [44][45][46] and PL of single layer WSe 2 .…”
Section: Introductionmentioning
confidence: 99%